The Identifying Factors Affecting Nursing Workload: A Literature Review - Diah Arruum; Sri Yulia; Muliyadi, Muliyadi; Nur Asiah (Jurnal Keperawatan Priority, 2024)
Nurses are essential in realizing quality health service management. This quality can be achieved if the quality of life of nurses is maintained and control is optimal. However, nurses in various work units still face workloads that result in disruptions to the quality of patient safety. The study aimed to identify factors Affecting Nursing Workload. The year used was 2019-2023, and the research design used all quantitative and qualitative research-data based on ProQuest, Pub Med, and Science Direct articles. The article was published in English, and nurses as a sample. Factors OR Aspect AND Affecting OR Influencing AND Workload OR “amount of work” OR “high workload” AND nurses. There were twelve articles included in this article. This article studies three themes: the effects of a high nursing workload on patient care, the impact of a high nursing workload on mental nurses, and other factors. A nurse’s workload can cause problems with patients, the mental health of nurses, and other factors. It requires commitment from leaders, managers, and nurses to provide patient care and services to improve the quality of nurses’ work and patient satisfaction.